The Effectiveness of Serial Casting in the Treatment of Recurrent Equinovarus in Children With Arthrogryposis. Issue 2 (1st February 2023) - Church, Chris; Bourantas, Christina; Butler, Stephanie; Salazar-Torres, Jose J.; Henley, John; Donohoe, Maureen; Miller, Freeman; Nichols, L. Reid Boyce
Abstract : Background: Arthrogryposis multiplex congenita (AMC) is characterized by joint contractures in 2 or more body areas, often resulting in clubfoot deformities that are typically stiffer than those seen in idiopathic clubfoot deformities. While surgery is routinely used to treat clubfoot in AMC, it has a high rate of recurrence and complications. Current literature suggests serial casting (SC) could be useful in treating clubfoot in AMC, though evidence of its effectiveness is limited. Methods: Passive range of motion (PROM), dynamic foot pressure, parent-reported Pediatric Outcomes Data Collection Instrument, brace tolerance, and the need for post-casting surgery were evaluated retrospectively in children with AMC treated with SC to address clubfoot deformities. Analysis of variance or paired t tests were used as appropriate on pre-casting, short-term (within 6 mo after SC) and/or longer-term (6 to 18 mo after SC) parameters to determine the effectiveness of SC. Brace tolerance before and after SC was analyzed using the Global Test for Symmetry, and medical records were reviewed to determine the need for surgery post-SC. Results: Forty-six children (6.1±3.1 y old) were cast an average of 2.5±1.9 times, resulting in 206 SC episodes. PROM showed improvement in ankle dorsiflexion and forefoot abduction in the short term ( P <0.05), returning to baseline measurements in the long term ( P =0.09). Brace tolerance improved after casting ( P <0.05). Only 15% of feet required surgery at follow-up at 10.3±5.5 years. There were no significant changes in dynamic foot pressure or Pediatric Outcomes Data Collection Instrument results after SC, except for an increase in the pain subtest ( P <0.05). Conclusions: Serial casting in children with AMC can be effective in temporarily improving PROM and improving brace tolerance, but it does not impact dynamic barefoot position. Positive impact of conservative management in children with AMC can potentially delay or reduce the need for invasive surgical intervention by improving PROM and brace tolerance. Level of Evidence: Level III, Retrospective Comparative Study.